1994
DOI: 10.1164/ajrccm.149.6.8004320
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of nasal and face mask continuous positive airway pressure.

Abstract: Studies of the hemodynamic effects of nasal continuous positive airway pressure (n-CPAP) in normal subjects have had conflicting results. The largest study (n = 19) found no effect of up to 15 cm H2O on heart rate (HR), cardiac stroke volume (SV), or cardiac index. We hypothesized that n-CPAP, by increasing intrathoracic pressure, should decrease SV and cardiac output (CO) in a dose-dependent fashion in normal subjects. We also hypothesized that mouth position, i.e., open or closed, could affect intrathoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 24 publications
(21 reference statements)
1
27
0
Order By: Relevance
“…In adults, CPAP reportedly has no effect on cardiac output up to 15 cm H 2 O, 29,30 and it decreases cardiac output at 20 cm H 2 O. 31 These data indicate that the effects of CPAP on cardiac output are dependent on the amount of pressure delivered, and may explain our finding that CPAP delivered at relatively low pressure did not affect cardiac output.…”
Section: Demographic Characteristicsmentioning
confidence: 54%
“…In adults, CPAP reportedly has no effect on cardiac output up to 15 cm H 2 O, 29,30 and it decreases cardiac output at 20 cm H 2 O. 31 These data indicate that the effects of CPAP on cardiac output are dependent on the amount of pressure delivered, and may explain our finding that CPAP delivered at relatively low pressure did not affect cardiac output.…”
Section: Demographic Characteristicsmentioning
confidence: 54%
“…Using ICG, we observed a reduction in both SV and CO under increasing nPAP levels. The application of PAP during invasive ventilation has long been known to suppress CO (43); however, results of previous experiments using noninvasive PAP ventilation have been inconsistent (28,37). PAP results in a reduction in volume in both the left and right ventricles, as has been shown by echocardiography (23) and magnetic resonance imaging (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the effects of augmented positive ITP, which occurs with positive airway pressure (PAP) ventilation, on cardiovascular autonomic control. The application of PAP, both invasively or noninvasively, increases ITP and may result in a reduction in cardiac filling pressures (23,29,37,43). A reduction in cardiac filling pressures associated with PAP (or positive end-expiratory pressure) may induce a compensatory increase in vascular resistance to maintain systemic arterial pressure in the face of a reduced cardiac output (CO) (5, 41).…”
mentioning
confidence: 99%
“…Hemodynamic responses reported after treatment with CPAP are variable; CPAP has been reported to reduce cardiac output in healthy subjects in a number of studies, although cardiac output is increased by CPAP in patients with poorly compensated congestive heart failure. 43,44 Conversely, it has also been reported that cardiac output may be reduced in some patients with severe congestive heart failure and that no effect is evident with CPAP in control subjects. 45,46 Renal blood flow and function have also been reported to decrease with increasing CPAP air pressure.…”
Section: Confirmation Of Initial Diagnosismentioning
confidence: 99%